Artificial Intelligence and Digital Dentistry:7 Takeaways - Dr Hisham Barakat, (DDS, MAGD, DABOI, FAAID) (International Dental Journal, 2023)
Introduction: A.I. and Digital Dentistry have transformed the way we practice, becoming the standard of care in many clinics across the US. Case Description: This presentation will discuss 7 key takeaways from using A.I. and Digital Dentistry in our day-to-day practice. Discussion: What we know today about A.I. & Digital Dentistry is a constantly evolving journey that requires continuous acclimation. We, as clinicians can leverage these new technologies, as well as Robotic Dentistry, to improve our services to patients, make our practices more efficient, and optimize our clinical outcomes. A.I. has mutilple applications, from integrating with imaging softwares to providing clinicians recommended diagnosis, second opinions, better treatment acceptance, and training opportunities for doctors. Moreover, A.I. helps with restorative design and 3D printing within minutes of taking an Intraoral Scan.Additionally, A.I. platforms can track incoming calls, analyze opportunties to optimize patient experiences and help analyze data and KPIs within the dental clinic itself. Specifically, for Implant Dentistry, the digital workflow from the intial scan to the final restortation can be pre-planned to make procedures predictable and enhance the clinical outcome. Ultimately, Digital Dentistry helps patients understand and take ownership of their own treatment modalities, including but not limited to, clear aligners, implants, full mouth reconstruction or procedures as simple as needing an occlusal guard. Conclusion/Clinical Description: Clinicians will gain a clear overview of these cutting edge technologies available today at their fingertips. These insights will assist in making decisions about best practices, providing a full understanding of what these technologies mean, and whether the return on these investments make sense.